A dual metal site covalent polymer catalyst and its preparation method and application
Through bimetal site covalent polymer catalyst, photogenerated electron hole pairs and metal catalytic activity centers are used to solve the problems of low reaction selectivity and pollution in traditional methods, achieving efficient conversion of aromatic alcohols into aromatic aldehydes, and improving Catalytic stability and yield.
Patent Information
- Application Number
- CN202410426661.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-04-10
AI Technical Summary
Traditional chemical methods have low reaction selectivity and low yield in the process of oxidizing aromatic alcohols to form aldehydes. The heavy metal oxidants used pollute the environment, have poor catalytic stability, and are difficult to recycle.
Using bimetal site covalent polymer catalyst, photon absorption by covalent polymers generates electrons and hole pairs, introduces bimetals to promote separation, reduces reaction barriers, activates reaction substrates, and achieves high efficiency and high selectivity of aromatic alcohols. Convert to aromatic aldehyde and has excellent catalytic stability.
The high efficiency and high selectivity of aromatic alcohol are achieved to convert aromatic aldehydes, and the catalyst has good stability and recycling ability, avoid heavy metal pollution, and improve yield and reaction efficiency.
Smart Images

Figure CN118320862B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and particularly relates to a bimetallic site covalent polymer catalyst and a preparation method and application thereof. Background Art
[0002] Aromatic aldehydes are an important class of organic substances. Traditional chemical methods are to oxidize alcohols to generate aldehydes or ketones through stoichiometric inorganic oxides. For example, chromium (VI) oxide, permanganate, ruthenium (VI) oxide, high-valent iodine oxide, etc. are used to oxidize alcohols to generate aldehydes or ketones. However, the activity of aldehydes is higher than that of alcohols, and stoichiometric oxidants can easily cause further oxidation of the product aldehydes to generate other by-products. Therefore, traditional chemical methods have lower reaction selectivity in the process of producing aldehydes, resulting in a low yield of the target aldehyde. Moreover, these oxidants are often heavy metal oxidants, which are relatively expensive, and are prone to produce heavy metal waste liquids, which seriously pollute the environment. They are also corrosive and highly dangerous. The catalysts used in the prior art to catalyze the conversion of aromatic alcohols into aromatic aldehydes have low catalytic activity, resulting in low product yields, and poor catalytic stability, and are often unable to be recycled.
[0003] Therefore, there is an urgent need to provide a new catalyst to replace the traditional oxidant or catalyst to oxidize aromatic alcohols to form aldehydes, and the new catalyst has high selectivity for the target product and high catalytic efficiency, thereby improving the yield of the target product. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. The present invention provides a bimetallic site covalent polymer catalyst and its preparation method and application. In the bimetallic site covalent polymer catalyst of the present invention, the covalent polymer itself generates electron and hole pairs after absorbing photons, and the introduced bimetal effectively promotes the separation of photogenerated electron-hole pairs. In addition, the metal acts as a catalytic active center, which can activate the reaction substrate and reduce the reaction barrier, thereby efficiently and selectively converting the aromatic alcohol into the corresponding aromatic aldehyde, and the bimetallic site covalent polymer catalyst of the present invention has excellent catalytic stability.
[0005] In order to solve the above problems, the present invention provides the following technical solutions:
[0006] A first aspect of the present invention provides a dual metal site covalent polymer catalyst.
[0007] A bimetallic site covalent polymer catalyst, the structural formula of which is shown below:
[0008]
[0009] The second aspect of the present invention provides a method for preparing a dual metal site covalent polymer catalyst.
[0010] A method for preparing a bimetallic site covalent polymer catalyst comprises the following steps:
[0011] (1) dissolving 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin and anhydrous acetate in an organic solvent, heating the mixture for reaction, and then extracting and filtering the mixture under reduced pressure to obtain a metal-coordinated porphyrin compound;
[0012] (2) dissolving the metal-coordinated porphyrin compound and 5,5'-dibromo-2,2'-bipyridine obtained in step (1) in a solvent, stirring, then adding tetrakis(triphenylphosphine)palladium and cuprous iodide, heating under a protective atmosphere, washing, obtaining a sample, and setting aside;
[0013] (3) Mixing the sample of step (2) with anhydrous chloride salt and ether to obtain a milky yellow solution, stirring the solution in an ice-water bath, and after the solution becomes clear, filtering and washing under reduced pressure, and then drying to obtain the bimetallic site covalent polymer catalyst.
[0014] Preferably, in step (1), the molar ratio of 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin to anhydrous acetate is 0.4:(0.4-1.2), more preferably 0.4:(0.8-1.0).
[0015] Preferably, in step (1), the anhydrous acetate salt is selected from at least one of nickel acetate, cobalt acetate and zinc acetate.
[0016] Preferably, in step (1), the organic solvent comprises at least one of N,N-dimethylformamide, chloroform and acetone, and further preferably, the organic solvent is N,N-dimethylformamide.
[0017] Preferably, in step (1), the temperature of the temperature-raising reaction is 120-145° C., and the time of the temperature-raising reaction is 3-4 hours.
[0018] Preferably, in step (2), the molar ratio of the metal coordinated porphyrin compound to 5,5'-dibromo-2,2'-bipyridine is 0.22:(0.1-0.5), more preferably 0.22:(0.2-0.3).
[0019] Preferably, in step (2), the molar ratio of the metal coordinated porphyrin compound to tetrakis(triphenylphosphine)palladium and cuprous iodide is 0.22:(0.005-0.01):(0.010-0.02), and more preferably 0.22:(0.005-0.008):(0.010-0.012).
[0020] Preferably, in step (2), the solvent is a mixed solvent of diisopropylamine and chloroform, and further preferably, the volume ratio of diisopropylamine to chloroform is 1:(4-10), more preferably 1:6.
[0021] Preferably, in step (2), the heating temperature is 75-85° C. and the heating time is 30-36 hours.
[0022] Preferably, in step (2), the protective atmosphere includes a rare gas or nitrogen, such as argon or helium.
[0023] Preferably, in step (3), the anhydrous chloride salt is selected from at least one of ferric chloride, palladium chloride and manganese tetrachloride.
[0024] Preferably, in step (3), the mass ratio of the sample in step (2) to anhydrous chloride salt is 100:(10-30), and more preferably 100:(20-25).
[0025] Preferably, in step (3), stirring is performed in an ice-water bath for 2-6 hours.
[0026] Preferably, a method for preparing a bimetallic site covalent polymer catalyst comprises the following steps:
[0027] (1) dissolving 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin and anhydrous acetate in an organic solvent, raising the temperature to 135-140° C. and reflux for 4 hours, and obtaining a metal-coordinated porphyrin compound through extraction and reduced pressure filtration procedures;
[0028] (2) dissolving the metalloporphyrin and 5,5'-dibromo-2,2'-bipyridine obtained in step 1 into a mixed solvent of diisopropylamine and chloroform. Then stirring at room temperature for a period of time, adding tetrakis(triphenylphosphine)palladium and copper (I) iodide thereto, heating at 80°C for 36 hours under an argon atmosphere, placing the obtained sample in a Soxhlet extractor, and washing with a mixed solvent for 3 days;
[0029] (3) adding the sample and anhydrous chloride salt in step 2 into a dry round-bottom flask, and then slowly adding a certain amount of ether to obtain a milky yellow solution, stirring for a period of time under ice-water bath conditions, and after the solution becomes clear, filtering under reduced pressure and washing with ether, and then vacuum drying to obtain the bimetallic site covalent polymer catalyst.
[0030] The third aspect of the present invention provides an application of a dual metal site covalent polymer catalyst.
[0031] Application of bimetallic site covalent polymer catalysts in the conversion of aromatic alcohols to aromatic aldehydes.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) In the bimetallic site covalent polymer catalyst of the present invention, the covalent polymer itself generates electron and hole pairs after absorbing photons, and the introduced bimetal effectively promotes the separation of photogenerated electron-hole pairs. In addition, the metal acts as a catalytic active center, which can activate the reaction substrate and reduce the reaction barrier, thereby efficiently and selectively converting the aromatic alcohol into the corresponding aromatic aldehyde. In addition, the bimetallic site covalent polymer catalyst of the present invention has excellent catalytic stability.
[0034] (2) The bimetallic site covalent polymer catalyst of the present invention has the advantages of both polymer and homogeneous catalysis. The polymer itself is tailorable and modifiable, and the diversity of material synthesis methods can achieve precise control of the structure of polymer materials. By introducing light-absorbing building units, the absorption of sunlight can be effectively increased; it has a large specific surface area and rich pore structure, which is beneficial to the adsorption of reactants and mass transfer during the reaction. The coordinated bimetallic acts as a catalytic active center and can effectively activate the reactants. The polymer structural characteristics and the advantages of bimetallic catalytic activity work synergistically to achieve efficient conversion of aromatic alcohols under visible light conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The transmission electron microscope image and element distribution map of the bimetallic site covalent polymer catalyst prepared in Example 1;
[0036] Figure 2 This is the infrared spectrum of the bimetallic site covalent polymer catalyst prepared in Example 1;
[0037] Figure 3 N2 adsorption-desorption curve of the bimetallic site covalent polymer catalyst prepared in Example 1;
[0038] Figure 4 This is a diagram of the cyclic catalytic effect of the dual metal site covalent polymer catalyst prepared in Example 1. DETAILED DESCRIPTION
[0039] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0040] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0041] The reaction process involved in the dual metal site covalent polymer catalyst is as follows:
[0042]
[0043] Example 1
[0044] A method for preparing a bimetallic site covalent polymer catalyst comprises the following steps:
[0045] (1) Take a 100 mL round-bottom flask, add weighed 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin (0.4 mmol), anhydrous nickel acetate (0.8 mmol), add 60 mL of N,N-dimethylformamide (DMF), replace the air with argon (i.e., set an argon environment), then raise the temperature to 140°C and reflux for 4 hours, add 100 mL of water, remove part of DMF under reduced pressure, extract the remaining solvent with water and dichloromethane, collect the organic phase, dry it with anhydrous sodium sulfate, remove dichloromethane under reduced pressure, add 100 mL of ethyl acetate, dissolve it completely by ultrasonication, filter, remove the filter cake, remove ethyl acetate under reduced pressure, and obtain a purple powder, which is named NiPor;
[0046] (2) 5,5'-dibromo-2,2'-bipyridine (0.22 mmol), NiPor prepared in step (1) (0.2 mmol), diisopropylamine (DIPA, 5 mL) and chloroform (30 mL) were added to a 100 mL round-bottom flask, and the air was replaced by argon under ultrasound for 10 minutes, and then degassed by thawing cycle for 3 times, and stirred evenly at room temperature for 12 hours. Tetrakis(triphenylphosphine)palladium (0.008 mmol) and copper (I) iodide (0.012 mmol) were added to the round-bottom flask, and heated at 80°C for 36 hours under argon. The obtained sample was washed with toluene, 1,4-dioxane, dichloromethane, and methanol in sequence, and then washed with a Soxhlet extractor containing dichloromethane for 3 days. The final sample was named NiPor-DPy;
[0047] (3) 100 mg of the NiPor-DPy sample prepared in step (2) and 24 mg of anhydrous ferric chloride were added to a dry 100 mL round-bottom flask, the air was replaced with argon, and the mixture was stirred at room temperature for 10 minutes. After stirring, 25 mL of ether was slowly added to obtain a milky yellow solution. The mixture was stirred in an ice-water bath for 2 hours, at which time the solution became clear. Stirring was continued for 4 hours, and stirring was stopped. The obtained solid was washed with ether and vacuum dried at 50° C. for 12 hours to finally obtain a bimetallic site covalent polymer catalyst, named NiPor-FeDPy.
[0048] Example 2
[0049] A method for preparing a bimetallic site covalent polymer catalyst comprises the following steps:
[0050] (1) Take a 100 mL round-bottom flask, add weighed 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin (0.4 mmol) and anhydrous nickel acetate (0.9 mmol), add 80 mL of N,N-dimethylformamide (DMF), replace the air with argon (i.e., set an argon environment), then raise the temperature to 145°C and reflux for 3.5 hours, add 100 mL of water, remove part of DMF under reduced pressure, extract the remaining solvent with water and dichloromethane, collect the organic phase, dry it with anhydrous sodium sulfate, remove dichloromethane under reduced pressure, add 100 mL of ethyl acetate, dissolve it completely by ultrasonication, filter, remove the filter cake, remove ethyl acetate under reduced pressure, and obtain a purple powder, which is named NiPor;
[0051] (2) 5,5'-dibromo-2,2'-bipyridine (0.22 mmol), NiPor (0.3 mmol) prepared in step (1), diisopropylamine (6 mL) and chloroform (32 mL) were added to a 100 mL round-bottom flask, and the air was replaced by argon under ultrasound for 10 minutes, and then degassed by thawing cycle 3 times, and stirred evenly at room temperature for 10 hours. Tetrakis(triphenylphosphine)palladium (0.007 mmol) and copper (I) iodide (0.010 mmol) were added to the round-bottom flask, and heated at 80°C for 36 hours under argon. The obtained sample was washed with toluene, 1,4-dioxane, dichloromethane, and methanol in sequence, and then washed with a Soxhlet extractor containing dichloromethane for 3 days. The final sample was named NiPor-DPy;
[0052] (3) 100 mg of the NiPor-DPy sample prepared in step (2) and 22 mg of anhydrous ferric chloride were added to a dry 100 mL round-bottom flask, the air was replaced with argon, and the mixture was stirred at room temperature for 15 minutes. After stirring, 25 mL of ether was slowly added to obtain a milky yellow solution. The mixture was stirred in an ice-water bath for 2 hours, at which time the solution became clear. Stirring was continued for 4 hours, and stirring was stopped. The obtained solid was washed with ether and vacuum dried at 50°C for 12 hours to finally obtain a bimetallic site covalent polymer catalyst, named NiPor-FeDPy.
[0053] Example 3
[0054] A method for preparing a bimetallic site covalent polymer catalyst comprises the following steps:
[0055] (1) Take a 100 mL round-bottom flask, add weighed 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin (0.4 mmol) and anhydrous nickel acetate (1 mmol), add 80 mL of N,N-dimethylformamide (DMF), replace the air with argon (i.e., set an argon environment), then raise the temperature to 135°C and reflux for 4 hours, add 100 mL of water, remove part of DMF under reduced pressure, extract the remaining solvent with water and dichloromethane, collect the organic phase, dry it with anhydrous sodium sulfate, remove dichloromethane under reduced pressure, add 100 mL of ethyl acetate, dissolve it completely by ultrasonication, filter, remove the filter cake, remove ethyl acetate under reduced pressure, and obtain a purple powder, which is named NiPor;
[0056] (2) 5,5'-dibromo-2,2'-bipyridine (0.22 mmol), NiPor (0.25 mmol) prepared in step (1), diisopropylamine (5 mL) and chloroform (30 mL) were added to a 100 mL round-bottom flask, and the air was replaced by argon under ultrasound for 10 minutes, and then degassed by thawing cycle 3 times, and stirred evenly at room temperature for 12 hours. Tetrakis(triphenylphosphine)palladium (0.009 mmol) and copper (I) iodide (0.015 mmol) were added to the round-bottom flask, and heated at 75°C for 32 hours under argon. The obtained sample was washed with toluene, 1,4-dioxane, dichloromethane, and methanol in sequence, and then washed with a Soxhlet extractor containing dichloromethane for 3 days. The final sample was named NiPor-DPy;
[0057] (3) 100 mg of the NiPor-DPy sample prepared in step (2) and 28 mg of anhydrous ferric chloride were added to a dry 100 mL round-bottom flask, the air was replaced with argon, and the mixture was stirred at room temperature for 10 minutes. After stirring, 25 mL of ether was slowly added to obtain a milky yellow solution. The mixture was stirred in an ice-water bath for 2 hours, at which time the solution became clear. Stirring was continued for 4 hours, and stirring was stopped. The obtained solid was washed with ether and vacuum dried at 50° C. for 12 hours to finally obtain a bimetallic site covalent polymer catalyst, named NiPor-FeDPy.
[0058] Comparative Example 1
[0059] Compared with Example 1, the difference of Comparative Example 1 is that an equal amount of 4,4-dibromobiphenyl is used to replace 5,5'-dibromo-2,2'-bipyridine in Example 1, and the rest of the process is the same as Example 1.
[0060] Product effect testing
[0061] The catalyst prepared in the above examples and comparative examples (dosage: 10 mg, denoted as "Cat") and the reaction substrate The concentration of 1,4-dioxane was 1 mmol, a 300W xenon lamp (i.e., "Visible Light") was used as the light source in a UVCUT 420nm filter, 1,4-dioxane was used as the solvent, the volume of 1,4-dioxane was 10 mL, and all reactions (recorded as "r, t") were carried out under an oxygen atmosphere. Aromatic alcohol oxidation experiments were carried out to obtain aromatic aldehyde products. The equation for the reaction is shown below:
[0062] The results obtained by catalyzing the above reaction using the catalyst prepared in Example 1 are shown in Table 1 (yield = actual yield / theoretical yield*100%), and the results obtained by catalyzing the above reaction using the catalyst prepared in Comparative Example 1 are shown in Table 2.
[0063] Table 1: Catalytic reaction results of Example 1
[0064]
[0065]
[0066] Table 2: Comparative Example 1 Catalyst Catalytic Reaction Results
[0067]
[0068] It can be seen from Table 1 and Table 2 that the catalytic effect of the catalyst prepared in Example 1 of the present invention on the conversion of aromatic alcohols into aromatic aldehydes is significantly higher than that of the catalyst prepared in Comparative Example 1.
[0069] Figure 1 The transmission electron microscope image and element distribution map of the bimetallic site covalent polymer catalyst prepared in Example 1; Figure 1 It can be seen that the elemental composition of the dual metal site covalent polymer catalyst prepared in Example 1.
[0070] Figure 2 The infrared spectrum of the bimetallic site covalent polymer catalyst prepared in Example 1; Figure 2 (The horizontal axis "Wavenumber" represents the wave number, and the vertical axis "Transmittance" represents the transmittance) It can be seen that the dual metal site covalent polymer catalyst is obtained by the reaction of nickel-coordinated porphyrin and iron-coordinated bipyridine building units.
[0071] Figure 3 N2 adsorption-desorption curve of the bimetallic site covalent polymer catalyst prepared in Example 1; Figure 3(The horizontal axis "Relative pressure" represents relative pressure, the vertical axis "N2 uptake" represents nitrogen absorption, "Adsorption" represents adsorption, "Desorption" represents desorption, and "STP" represents standard temperature and pressure) It can be seen that the prepared bimetallic site covalent polymer catalyst has a rich pore structure and a large specific surface area.
[0072] Figure 4 This is a diagram of the cyclic catalytic effect of the bimetallic site covalent polymer catalyst prepared in Example 1; Figure 4 The catalyst of Example 1 is used in a cyclic catalytic manner according to the reaction numbered 1 in Table 1. Figure 4 (The horizontal axis "Cyclenumber" represents the number of cycles, and "Yield" represents the yield) It can be seen that the dual-metal site covalent polymer catalyst prepared in the embodiment of the present invention has good cycle stability.
[0073] The effects of the catalysts prepared in other examples on catalyzing the conversion of aromatic alcohols into aromatic aldehydes are similar to those in Example 1.
[0074] The above content describes the basic principle and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that protection scope of the present invention is not limited by the above-described embodiments. Without departing from the spirit and scope of the present invention, the present invention also has various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed for protection.
Claims
1. Application of a bimetallic site covalent polymer catalyst in the conversion of aromatic alcohols into aromatic aldehydes, wherein the structural formula of the bimetallic site covalent polymer catalyst is as follows: The preparation method of the bimetallic site covalent polymer catalyst comprises the following steps: (1) dissolving 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin and anhydrous nickel acetate in an organic solvent, heating the mixture for reaction, and then extracting and filtering the mixture under reduced pressure to obtain a metal-coordinated porphyrin compound; (2) dissolving the metal-coordinated porphyrin compound and 5,5'-dibromo-2,2'-bipyridine obtained in step (1) in a solvent, stirring, then adding tetrakis(triphenylphosphine)palladium and cuprous iodide, heating under a protective atmosphere, washing, obtaining a sample, and setting aside; (3) Mixing the sample of step (2) with anhydrous ferric chloride and diethyl ether to obtain a milky yellow solution, stirring the solution in an ice-water bath, and after the solution becomes clear, filtering and washing under reduced pressure, and then drying to obtain the bimetallic site covalent polymer catalyst.
2. The use according to claim 1, characterized in that: In step (1), the molar ratio of 5,10,15,20-tetrakis(4-ethynylphenyl)porphyrin to anhydrous nickel acetate is 0.4:(0.4-1.2).
3. The use according to claim 1, characterized in that: In step (1), the temperature of the temperature-raising reaction is 120-145° C., and the time of the temperature-raising reaction is 3-4 hours.
4. The use according to claim 1, characterized in that: In step (2), the molar ratio of the metal coordinated porphyrin compound to 5,5'-dibromo-2,2'-bipyridine is 0.22:(0.1-0.5).
5. The use according to claim 1, characterized in that: In step (2), the molar ratio of the metal coordinated porphyrin compound to tetrakis(triphenylphosphine)palladium and cuprous iodide is 0.22:(0.005-0.01):(0.010-0.02).
6. The use according to claim 1, characterized in that: In step (2), the heating temperature is 75-85° C. and the heating time is 30-36 hours.
7. The use according to claim 1, characterized in that: In step (3), the mass ratio of the sample in step (2) to anhydrous ferric chloride is 100:(10-30).
